Pengaruh Jenis dan Lama Pengeringan Terhadap Rendemen, Kadar Air, dan Mutu Mikrobiologi Cumi-Cumi (Loligo sp.) Utuh Kering - HANDAYANI, BAIQ RIEN; Werdiningsih, Wiharyani; Nurul Wahida, Baiq Naila (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2025)
This study aimed to determine the effect of drying method and duration on the yield, moisture content, and microbiological quality of dried squid (Loligo sp.). A randomized block design was used with two factors: drying method (sun drying and greenhouse drying) and drying time (16, 20, 24, and 28 hours). Parameters measured included yield, moisture content, total plate count, total coliform count, total mold count, and visual fungal growth during storage. Yield and moisture content data were analyzed using ANOVA, followed by Tukey's HSD test at a 5% significance level. Microbiological parameters were evaluated descriptively. The results indicated that neither drying method nor drying time significantly affected the yield. However, drying time had a significant effect on moisture content. Total plate counts in all treatments exceeded the Indonesian National Standard (SNI), while total coliform and mold counts remained within acceptable limits. The best quality was obtained with greenhouse drying for 24 hours, resulting in a yield of 15.47%, moisture content of 15.93%, a total plate count of 7.4 × 105 CFU/g, a total coliform count of <1.0 × 101 CFU/g, and a total mold count of <1.0 × 102 CFU/g.